Labour costs in the aerospace industry: LMDI decomposition of aerospace manufacturing payrolls - Machay, Martin; Hajko, Vladimír (Koszty pracy w przemyśle lotniczym: LMDI, rozkład płac za produkcję lotniczą, 2020)
A novel approach to aggregated payroll data analysis using the logarithmic mean Divisia index decomposition is applied to the US Aerospace manufacturing industry during the period of 1998 to 2012, both in nominal and real terms. The period covered improves the understanding of how the aerospace manufacturing industry deals with severe economic blows in the area of the most important factor of production, namely labour. The decomposition was based on three factors: the wage effect, the size and the number effect. The results show that the wages are less influential than the restructuring processes when considering the aggregated payroll. Unlike what simple wage indices suggest, the wage effect in real terms contributed only to a moderate increase in payrolls by a factor of 1.15, which is about the same contribution resulting from the increasing number of firms in the industry. The cumulative size effect in the investigated period was about 0.647. The results show that the relatively stable real labour costs of the US aerospace industry were a consequence of the shrinking size of firms which compensated the growth of average wages
Ekonomia XXI Wieku = Economics of the 21st Century, 2020, Nr 23, s. 56-75